Multifunctional optical devices based on 5x5 multimode interference on an SOI platform for all-optical computing applications - - Thanh Le, Trung (Vietnam Journal of Science and Technology, 2017)
The design of multifunctional devices based on Multimode Interference (MMI) structures for all-optical computing applications is presented in this paper. Based on the self-imaging effect in a multimode silicon planar waveguide, a variety of all-optical devices such as all-optical beam splitters, combiners, optical XOR and OR logic gates can be realized. The analytical expression describing the characteristics of the proposed devices is analysed and derived. Designs of the proposed devices on a silicon on insulator (SOI) platform are then verified and optimised using numerical simulation methods